아편양제제에 의해 유발된 오심구토의 예방에 대한 내관자침의 효과 - 이수경(Su Kyung Lee); 이시우(Si Woo Lee); 최덕화(Deok Hwa Choi) (동의생리병리학회지, 2007)
There is growing interest in the use of nonpharmacologic approaches to prevent postoperative nausea and vomiting. This study was designed to investigate the effect of acupuncture on P6 for preventing Opioid-induced nausea and vomiting. A total of 83 patients receiving intravenous patient controlled analgesia(PCA) with fentanyl were randomly assigned to two groups. In acupuncture group, they've got treatment after surgery at recovery room for 20minutes. Assessment of nausea and vomiting was obtained from all patients for 48hours. The incidence of nausea, that of vomiting and the nausea grade-the severity of nausea within 48 hours after surgery- were the main outcome measures which showed no statistically significant difference between groups. There is no sufficient evidence to suggest effect of acupuncture on P6 for preventing PONV.